Hepatitis C Virus and infertility - Khalil, Noor AL-Huda; Mohammed, Ahmed (University of Thi-Qar Journal of Science, 2022)
Infertility is defined by inability to conceive after one year or more of unprotected sexual intercourse. Its causes by several causes including viruses such as Hepatitis C Virus. Hepatitis C Virus is sexually transmitted virus effect on reproductive system in male and female and caused infertility. The aim of study was to finding the correlation between Hepatitis C Virus and infertility. Case control study using ELISA technique for 90 serum samples, 50 patients with infertility (males and females) selected from private laboratories in Al-Nasiriya city from November 2021 to February 2022. Inclusion criteria of subjects include male and female patients who have infertility with age range 16-46 years old. The diagnosis was based on the clinical and laboratory examinations under the supervision of a specialist physician. The control group included 40 adults per some (males and females) who have children and look healthy. Both patients and control group received a set of questions. The results showed mean age of patients and control in this study was 30.62 with higher infertility rate 43-46 years old. The results detection of anti–HCV IgM antibody the infection percentage in male was highest (92.00%) than in female. On the other hand, detection of anti–HCV IgG antibody appear the infection in female was greater (24.00%) than in male. Hepatitis C Virus (HCV) considered as risk factor to cause infertility in male and female by affecting reproductive functions in both sexes.